Penggunaan Probiotik pada Budidaya Ikan Lele Sangkuring (Clarias sp.) di Drum Plastik di Desa Arisan Jaya, Ogan Ilir, Sumatera Selatan - Ade Dwi Sasanti; Septika Putri Anggraini (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Sasanti AD, Anggraini SP. 2019. The utilizing of probiotics for catfish sangkuriang (Clarias sp.) cultivation in plastic pond at Arisan Jaya Village Ogan Ilir, South Sumatera. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):134-140. The research was to provide information to farmers on the use probiotics on catfish (Clarias sp.). The used of probiotics aimed to maintain balance pathogenic microbes and suppress activity in the digestive tract , and the environmental biodegradation waters through the process. This study aimed to compare of field Practice is to provide information to the people about the utilizing of probiotics for catfish (Clarias sp.) cultivation a plastic drums at Arisan Jaya village Ogan Ilir. The research used two plastic drum media as a catfish maintenance container, the first maintenance container there was no addition of probiotics, while in the second maintenance container there was the addition of probiotics. The parameters were observed in this study were absolute weight growth, absolute the length growth, survival, and water quality. The result of this research showed that growth of catfish cultivation in plastic pond with length of 3,51cm and weight of catfish the used probiotics of 17,15 g was higher than the growth length of 2,46 cm and weight of catfish were not using probiotics of 12,03 g. The survival rate of the catfish utilizing of probiotics cultivation in plastic drums with the use probiotics and not use probiotics was 100%.